AYURVEDIC MANAGEMENT OF SUBLINGUAL CYST (BLANDIN NUHN MUCOCELE) - A CASE REPORT - Chary, *B.Harinatha; Prasuna, S.Gnana (International Journal of Ayurveda and Pharma Research, 2017)
Ayurveda has enumerated so many Mukharaogas (diseases of the oral cavity). Among these Jihwagata rogas (diseases of the tongue) were described separately. Susruta and Vagbhata had mentioned five Jihwagata rogas. Upajihwika told by Sushruta and Adhijihwa told by Vagbhata represent the cystic lesions on the ventral aspect of the tongue. Western science describes a few diseases in which the patient presents with cystic swelling on the under surface of the tongue. Blandin nuhn mucocele is one such disease. Mucocele is a cystic lesion or a cavity filled with mucus. They are found on any mucosal surface where underlying accessory glands are present. Mucoceles are commonly found in the lower lip and are very rarely found on the tongue. Cystic lesions or mucoceles on the ventral aspect of the tongue are less frequent. Many modern treatment modalities as surgical excision, cryosurgery and electro-cautery are the only choice of treatment to completely remove the lesion and reduce the chances of occurrence. Herewith we report a case of Adhijihwa (Blandin Nuhn Mucocele) according to Ayurveda. Ayurvedic internal medicines have provided promising results in reducing the cyst completely without causing any adverse effects within two months. Till this date there is no recurrence of the disease. Ayurvedic treatment helped in complete management without any surgical procedures.